LITERASI FITUR DATA-FORM MS. EXCEL UNTUK MENGELOLA DATABASE ANGGOTA PERKUMPULAN KEMATIAN “LAZARUS” MALANG - Rr. Tri Istining Wardani; Asminah Rachmi; Dwi Sudjanarti; Umi Khabibah; Achmad Zaini (P3M Politeknik Negeri Malang, 2022)
This community service aims to develop technical skills in managing databases. So far, the “Lazarus